Modelo deposicional das formações ferríferas bandadas hospedeiras de ouro no greenstone belt arqueano Rio das Velhas, Quadrilátero Ferrífero, com base em geoquímica e análises in situ de magnetita por ablação a laser via ICP-MS - Joanna Chaves Souto Araújo (2018)
Petrographic and geochemical studies were undertaken on some of the several Algoma-type banded iron formations from the Rio das Velhas greenstone belt, Quadrilátero Ferrífero, Brazil, including a number of samples from BIF-hosted gold deposits. These rocks show a great diversity in terms of primary mineralogy, lithological associations and geochemistry. The significant positive Eu anomalies (Eu/Eu*PAAS = 1.57-4.01) and comparatively lower contents of immobile elements (Al2O3 = 0.01-0.34 wt%, TiO2 = 0.01-0.02 wt%), of the carbonaceous and/or ferruginous chert layers of the Lamego and Urubu deposits, suggest that these had the highest contribution of hydrothermal fluid in their formation, with insignificant detrital input. The carbonate and-or magnetite-rich banded iron formation of the Cuiabá, Roça Grande, Ápis and Raposos deposits presents an intermediate contribution of hydrothermal fluid, as well as relatively low detrital input (Eu/Eu*PAAS = 1.34-3.25; Al2O3 = 0.04-1.47 wt%, TiO2 = 0.01-0.03 wt%). Banded iron formation with greater mineralogical variability including magnetite, carbonate and iron-rich silicates are present within the São Bento deposit, as well as the Campo Grande and Sumidouro non-mineralized banded layers. These layers have a high detrital input and low hydrothermal fluid influence (Eu/Eu*PAAS = 1.10-2.60; Al2O3 = 0.11-6.82 wt%, TiO2 = 0.03-0.33 wt%). Magnetite grains from selected samples from São Bento, Campo Grande, Sumidouro and Lamego are characterized according to textural relations and associated mineralogy in: Mag1 - diagenetic; Mag2 - early-stage hydrothermal; Mag3 and Mag4 - main-stage hydrothermal. Laser ablation ICP-MS analysis of magnetite indicates a systematic variation in Ti, V, Ni and Co contents, with Mag1 having the highest concentrations of these elements. The even higher trace element content of the Sumidouro diagenetic magnetite is related to an important clastic input to seawater during the deposition of this banded iron formation. The chemical composition of hydrothermal magnetite is largely dependent on coexisting minerals, such as sulfides, carbonates and silicates, and on the type of mechanism by which the magnetite formed (dissolution and reprecipitation, or re-equilibration). A depositional model is proposed suggesting that banded iron formation with mineralogical and geochemical diversity was deposited in different locations within the Rio das Velhas Archean basin. Chert layers were formed close to the hydrothermal source; carbonate and-or magnetite-rich banded iron formation were deposited further away from the volcanic center; and the silicate-carbonatemagnetite-rich banded iron formation were localized far from the hydrothermal vents in association with submarine fans with episodic input of clastic sediments. The banded iron formation types with abundant iron-rich carbonate and-or magnetite host gold mineralization more efficiently since they are especially favorable to sulfide replacement accompanied by gold precipitation.